(untitled) (Atti del Sodalizio Glottologico Milanese, 2014)
The etymology of the Germanic stem *paþa- > engl. paþ / pað is taken into consideration and the usual explanation as a Celtic or as an Iranic loan is rejected in favour of a viewpoint that tends to see *paþa- as an original Germanic stem, to be confronted with the Latin verb batuo. In fact, this proposal is in line with a treatment of *paþa- along with a traditional comparative analysis in terms of the Grimm’s law. KEYWORDS: Germanic, Latin, etymology, historical linguistics, reconstruction